IMPACT OF CLARIFYING AGENTS ON THE OPTICAL CLARITY OF PIGMENTED POLYPROPYLENE RESIN: A COMPLIANCE AND MIGRATION STUDY - Wulansari, Isma; Azhari, Mohamad Yusuf (Tanjungpura University, 2025)
Efforts to improve visual clarity and color stability in polypropylene (PP)-based products are carried out by adding clarifying agents, namely a sorbitol-based clarifying agent (PA) and a dibenzylidene sorbitol clarifying agent (NX), which function to accelerate crystal nucleation in within the polymer matrix. PP is widely used for packaging and automotive applications due to its clarity and transparency. This study was conducted to examine compliance and migration studies, assessing the suitability of the additives against quality standards and their migration stability. Migration tests were conducted visually using polyvinyl chloride (PVC) sheets at 55°C, with a 16-hour heating process. Additionally, a complaint analysis based on a digital prototype form was developed to identify the root causes of customer complaints related to color inconsistency, using the 4M approach (Man, Material, Machine, Method). The formulation includes dye pigments (small in size and easily migratable), organic pigments (more stable), and polyethylene wax as an internal lubricant. The results showed that 6 out of 7 samples with dye pigments experienced color migration (intensity 1–2), while organic pigments showed no migration (intensity 0). Clarifying agent improved clarity but failed to prevent pigment migration. Findings suggest that future research should focus on optimizing clarifying agents and additives to enhance pigment stability and durability.